Leptospira spp. in dairy cattle in a family farming system - Curci, Vera Cláudia Magalhães; Magajevski, Fernanda Senter; Moreli, Fernando Christiano Gabriel; Romaldini, Adriana Hellmeister de Campos Nogueira; da Costa, Ricardo Lopes Dias; de Oliveira, Talita Carolina Bragança [UNESP]; Cardoso, Tereza Cristina [UNESP]; Manzini, Suzane [UNESP]; Cavalheiro, Maria Eduarda [UNESP]; Alexandrino, Marcela [UNESP]; Bertozzo, Thainá Valente [UNESP]; Steinle, Jackieline Sampaio [UNESP]; et al. (Medicina Veterinaria (UFRPE), 2024)
Leptospirosis is an endemic zoonosis in Brazil responsible for numerous reproductive and economic losses to the dairy industry. Brazil ranks fifth in global production of cow's milk, by and around 23 million cows are milked every day. The northwest region of the state of São Paulo has a large number of family farming settlements, with dairy farming being predominant. This article reports a seroepidemiological study to detect agglutinins against Leptospira spp. in 1,004 dairy cattle kept on 64 family farms producing milk in the northwest region of São Paulo. Management and environmental data for situational diagnosis were obtained through a questionnaire. Antibodies against Leptospira spp. were investigated by the microscopic agglutination test (MAT) and milk and urine samples were obtained from seroreactive animals with titer ≥400. These samples were submitted to molecular tests. Of the 64 farms studied, 63 (98%) had seroreactive animals. Of the 1,004 animals, 523 (52%) were reactive. According to the molecular tests, the presence of Leptospira spp. in the urine and milk of the seroreactive animals was negative. Presence of wetlands, rodents, dogs, cats and horses and occurrence of abortion were variables associated with the risk of infection by Leptospira spp. In addition to its importance in animal health, leptospirosis poses a risk to human health, a situation that indicates the need for improvement of sanitary conditions in small farms.
Leptospira spp. em bovinos leiteiros criados em sistema de agricultura familiar
Keywords: Antibodies; Diagnosis; Leptospirosis; Zoonosis